Sistem Pakar Berbasis Android Dengan Metode Forward Chaining Untuk Mengidentifikasi Penggunaan Jenis Narkoba - Dhany Faizal Racma; Carolina Ety Widjayanti; Suyudi Suyudi (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2020)
The National Narcotics Agency or NNA is a Non-Ministry Government Institution (NMGI) Indonesia that has the task of carrying out government duties in the areas of prevention, eradication of psychotropic abuse and illicit circulation, precursors and other addictive ingredients except addictive ingredients for tobacco and alcohol. The National Narcotics Agency also has a function to handle and rehabilitate drug users. Banyumas National Narcotics Agency has problems, namely experts who are limited and not always in place in the service and drug tests is not effective, a solution is to create an information system, namely an expert system that is used to identify the types of drugs based on the user's physical characteristics. The method used in this study is Prototype. The programming languages used are PHP and C #, and use the MySQL database. The research results from the benefit test tested to 30 respondents produced a high percentage for system usability, easy to learn, efficiency, and the system could be accepted, while the results of hypothesis testing in this study were H1 which was accepted where there was a significant time difference between before and after using an Android-based Expert Identification System for Types of Drugs. Thus, this expert system can be used to assist in identifying types of drugs so that they are more effective and efficient than conventional methods.